Fuel metabolism during sepsis and injury - Frayn, K (1987)
Injury or sepsis cause changes in energy and protein metabolism affecting the entire body. These changes occur in a number of phases. The early period after injury, the 'ebb phase', is characterised by rapid mobilisation of stored fuels but little or no elevation of metabolic rate. This is followed by the more prolonged 'flow phase', characterised by increased metabolic rate and general catabolism. At all times the metabolic changes represent a complex interaction between the body's endogenous responses and the treatment given to the patient. Increased understanding of these responses is now allowing the nutritional treatment of septic and injured patients to be put onto a rational footing.